Blood Pressure Mediated the Effects of Urinary Uromodulin Levels on Myocardial Infarction: a Mendelian Randomization Study. Issue 11 (25th August 2022) - Jian, Zhongyu; Yuan, Chi; Ma, Yucheng
Abstract : Background: The causal links between urinary uromodulin (uUMOD) and cardiovascular disease (CVD) are still not clarified. Methods: We first assessed the relationship between uUMOD and CVD using bidirectional 2-sample Mendelian randomization. Then, multivariable Mendelian randomization and product of the coefficients methods were used to investigate the role of blood pressure in mediating the effect of uUMOD on CVD. Results: 1-unit higher uUMOD level was associated with a higher risk of myocardial infarction (MI), with an odds ratio of 1.08 ([95% CI, 1.02–1.14]; P =0.009), while MI was not associated with uUMOD levels in reverse. Our study did not support the causal effects of uUMOD on other CVD outcomes, including coronary artery disease, atrial fibrillation, heart failure, and ischemic stroke. In multivariable Mendelian Randomization, the direct effects of uUMOD on MI were attenuated to null after introducing systolic blood pressure or diastolic blood pressure. Mediation analysis showed that the indirect effect of uUMOD on MI mediated by systolic blood pressure or diastolic blood pressure was 1.05 ([95% CI, 1.04–1.06]; mediation proportion=69%) and 1.07 ([95% CI, 1.05–1.08]; mediation proportion=87%), respectively. Similar results were found in sensitivity analysis based on different sets of genetic instruments. Conclusions: Our findings provide evidence for the effect of higher uUMOD on increasing blood pressure, which mediates a consequent effect on MI risk in the general population. Further studies are necessary to verify the associations between uUMOD and other CVD outcomes.